Enabling cyber-physical systems for industry 4.0 operations: a service science perspective - Da Silva, A. (2021)
Based on the Internet of Things (IoT) and Smart Technologies, manufacturing industries are witnessing the fourth Industrial Revolution, Industry 4.0 (I4.0), and digital transformation is a keystone in this change. Cyber-Physical Systems (CPS) are strategic in thoroughly digitalizing companies, and I4.0 operations depend on CPS efficiency. Digital plants are held by digital technologies that provide excellent tools for improving product security and supply chain security but requires structured information management to maintain the CPS in its highest level of efficiency. These systems are overly complex and hard to handle when several CPS need to be combined as in a large factory, where several machines must work together to achieve a common goal. This research addresses these issues, and we propose an information management framework of industrial CPS that, towards the industrial efficiency, affords an increase in value for all stakeholders. The framework structures the information through the introduction of two innovative value co-creation concepts: (i) Fingerprint (FP-I4.0), a virtual vehicle that can carry two types of structured information and (ii) Cockpit4.0, an interaction entity between the various service systems, applied from cradle-to-cradle. Validated through the Service Science Theory, we conclude that the proposed empirical framework may boost up CPS efficiency and, from it, I4.0 operations will be more effective.